A clinical study of respiratory distress in neonates - Meena, Ramkesh; Kobal, Mallikarjun R.; Dhanwadkar, Sharanabasappa S.; N. B., Ashwini Kumari (International Journal of Contemporary Pediatrics, 2019)
Background: Respiratory distress is a medical emergency responsible for most of the admissions in NICUs during neonatal period. It is a major contributor to neonatal morbidity and mortality and results from a variety of respiratory and non-respiratory etiology. It occurs in 0.96 to 12% of live births and responsible for about 20% of neonatal mortality. Aim of study to find out the proportion of patients with different etiology of respiratory distress in neonates. Methods: The present study is a prospective, descriptive study which was carried out at neonatal units attached to SMS Medical College, Jaipur. All the neonates with respiratory distress admitted in NICU admitted from April 2012 to March 2013were selected for the present study. Detailed history including antenatal history, natal history, postnatal history with thorough clinical examinations and investigations done in each case and were recorded in the performa. Results: A total of 500 neonates were admitted and among them 375 were inborn (delivered in our hospitals) and 125 out-born (referred to our hospitals from outside). In inborn group hyaline membrane disease (HMD) was the most common cause (32%) of respiratory distress and in out-born congenital pneumonia/septicaemia (34.4%). There was male preponderance in both inborn and out-born groups with male: female ratio 1.45:1 and 1.6:1 respectively. Conclusions: Majority of cases in both inborn and out-born groups were preterm (56.8% and 54.4% respectively) which emphasises the need for care of mother during antenatal period for prevention of premature delivery.